KEPEMIMPINAN DAN BUDAYA ORGANISASI DI ERA 5.0“ Artualisasi Service Excellent Dalam Layanan Perbankan Syariah” - Raudatul, Eneng; Syugianto, Ahmad; Silalahi, Betrick; Suhendra, Iman; Wirdaneti, Wirdaneti (MAJU : Indonesian Journal of Community Empowerment, 2025)
The era of Society 5.0 requires organizations, including Islamic banking, to be able to adapt to technology without ignoring human values. This research aims to examine how adaptive leadership and organizational culture can encourage the actualization of service excellence in Islamic banking services. Service excellence is an essential requirement in the banking industry, including Islamic banking that emphasizes Islamic values. This research aims to analyze the actualization of service excellent principles in Islamic banking and how the application of Islamic values strengthens customer loyalty and satisfaction.  This activity was carried out through education and interactive discussions with students of SMK Yapia Parung on April 24, 2025. The results of the activity showed that an understanding of service excellence associated with Islamic leadership values and superior work culture was able to increase participants' insights into the importance of value-based services in the world of banking work.